Student Decision Making Factors in Choosing an Arabic Language Education Study Program at the Darul Ulum Kandangan Islamic Institute - Afifah, Nor; Fauziyah, Eka Putri (Assyfa Journal of Multidisciplinary Education, 2024)
Arabic Language Education is one of the most popular study programs at the Darul Ulum Kandangan Islamic Institute, many students make Arabic Language Education their first choice when choosing a study program, there are several things that underlie them choosing the Arabic Language Education study program as their first choice including previous educational background, interest in Arabic culture, ideals and motivation from parents and teachers. However, when lectures begin, not all students feel that their choice is right. Difficulty in understanding the material, friendship environment, and changes in lecture schedules cause some students to choose to move to other study programs. The purpose of this study was to determine the decision-making factors for students in choosing an Arabic language education study program at the Darul Ulum Kandangan Islamic Institute. The results showed that 90% of Arabic Language Education students made the Arabic Language Education study program their first choice when choosing a study program. In terms of the accuracy of choosing the Arabic Language Education study program, 70% of students felt it was right, 10% felt it was less right, and 20% felt it was not right